ANALISIS POLA CURAH HUJAN DI WILAYAH SUMATERA BAGIAN UTARA MENGGUNAKAN FAST FOURIER TRANSFORM (FFT) - Risa Albeta; Ishkaq Iskandar; Hamdi Akhsan; Suhadi (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2024)
This research was conducted in North Sumatra, namely at Iskandar Muda, Malikussaleh and Deli Serdang stations in the period 1885 to 2019. The purpose of the study was to analyze seasonal and interannual rainfall patterns. The method used is Fast Fourier Transform (FFT) and correlation between rainfall, sea surface temperature and wind. The results of the study showed that the rainfall pattern at Iskandar Muda, Malikussaleh and Deli Serdang stations had two peaks of rainfall. The peak rainfall of the three stations occurs in May and the second peak has differences between Deli Serdang and Iskandar Muda and Malikussaleh stations. Where the peaks of high periodization are only in the 6-month and 12-month periods. There is also a peak periodogram from each station seen in 18-30 months. Rainfall periodogram analysis shows the magnitude of data frequency for each phase cycle and its frequency. The correlation between rainfall, wind and sea surface temperature (SST) at the three stations has a different pattern. At Deli Serdang station, there is an influence of ENSO and IOD, while at Iskandar Muda and Malikussaleh stations there is no influence of ENSO and IOD. Then in the September, October, November (SON) season at the three stations there is no visible influence of ENSO and IOD.